Developing a Web-Based Virtual Tour for Smart Tourism Information in the Malioboro Area - Intan Anisa Sholikhah; Dwi Wahyuningrum (Jurnal Ilmiah Multimedia dan Komunikasi, 2026)
Malioboro is one of the most prominent urban tourism corridors in Yogyakarta, attracting a large number of domestic and international visitors. Despite its popularity, access to integrated digital information regarding essential public facilities remains limited, potentially reducing visitor convenience and mobility within the area. This study aims to develop a web-based virtual tour system that integrates spatial information on public facilities to support smart tourism services in the Malioboro area. The system was developed using the Multimedia Development Life Cycle (MDLC), which consists of six phases: concept development, design, material collection, system assembly, testing, and distribution. High-resolution 360° panoramic images and spatial data of public facilities were collected through field surveys and integrated into an interactive virtual tour platform equipped with a web-based map for spatial navigation. The developed system enables users to virtually explore the Malioboro area while accessing location-based information and navigation support through an immersive interface. Functional testing confirmed that all system features operated as intended, while a usability evaluation involving 50 respondents yielded a System Usability Scale (SUS) score of 84.75, indicating high usability and strong user acceptance. The findings demonstrate that integrating immersive virtual tour technology with interactive web map-based public facility information can support destination exploration while improving access to practical tourism information. This study highlights the potential of virtual tours to function not only as promotional media but also as interactive tourism information systems that support smart tourism implementation in urban destinations.